A Zn(ii) metal–organic framework with dinuclear [Zn2(N-oxide)2] secondary building units. Issue 19 (28th February 2019) - Ochi, Rika; Noro, Shin-ichiro; Kubo, Kazuya; Nakamura, Takayoshi
Abstract : A three-dimensional metal–organic framework with unprecedented [Zn2 ( N -oxide)2 ] secondary building units was synthesized using 3, 5-pyridinedicarboxylic acid N -oxide. Abstract : We report the synthesis, structural characterisation, and adsorption properties of a three-dimensional metal–organic framework [Zn(pydcao)(DMF)] (H2 -pydcao = 3, 5-pyridinedicarboxylic acid N -oxide) that has an unprecedented [Zn2 ( N -oxide)2 ] secondary building unit.